Altered Octopamine synthesis impairs tyrosine metabolism affecting Helicoverpa armigera vitality - Patil, Yogita P.; Wagh, Deepti S.; Barvkar, Vitthal T.; Gawari, Shyam K.; Pisalwar, Priyanka D.; Ahmed, Shadab; Joshi, Rakesh S. (Pesticide Biochemistry and Physiology, 2025)
Tyramine (1-hydroxylase (T(1H) is a key enzyme in the biosynthesis of octopamine (OA), a vital neurohormone in invertebrates. This study explores the expression patterns and functional role of Helicoverpa armigera T(1H (HaT(1H) across various tissues and developmental stages. HaT(1H expression was highest in the head and adult male stages, reflecting tissue-specific and developmental regulation. HaT(1H silencing significantly increased locomotion and decreased feeding behavior. OA supplementation in silenced insects or HaT(1H overexpression showed a contrary effect on locomotory and feeding behavior. In silico screening and inhibitory assays identified tomatidine, a tomato-derived metabolite, as a potent HaT beta H inhibitor with strong binding affinity. In vivo bioassays confirmed tomatidine's inhibitory effects, reducing feeding and increasing mortality in H. armigera. Modulation in HaT(1H expression or activity disturbs the tyrosine metabolic pathway, with altered levels of tyramine, octopamine, and dopamine. These results highlight HaT(1H as a key regulator of OA biosynthesis, influencing insect feeding, locomotion, and overall survival. The present study also introduces tomatidine as a potential candidate for insect control, given its ability to disrupt HaT beta H function. This work provides new insights into the physiological roles of HaT beta H and offers promising avenues for developing targeted pest management strategies.
Keywords: Helicoverpa armigera; Octopamine biosynthesis; Tomatidine; Tyramine (1-hydroxylase (HaT(1H); Tyrosine metabolic pathway